Analisis Kerentanan Tanah di Selatan Zona Longsor Desa Kalongan, Kabupaten Semarang Menggunakan Metode Horizontal to Vertical Spectral Ratio (HVSR) - Helena, Nahda Helena Sekarsari; Wuri Handayani (Jurnal Stasiun Geofisika Sleman, 2024)
The Semarang Regency, despite being far from the subduction zone in the southern part of Java Island, still faces the threat of landslides. One of the vulnerable areas is Kalongan Village, East Ungaran Sub-district, which experienced a significant landslide in 2022. The high potential for damage in residential areas underscores the need for a soil vulnerability analysis based on geophysical parameters. This study employs the microtremor method with Horizontal to Vertical Spectral Ratio (HVSR) analysis to determine dominant frequency, amplification factor, and seismic vulnerability index parameters. Data processing was conducted using Geopsy software, resulting in 2D and 3D contour maps. The results indicate that the dominant frequency in this area is low (<2.5 Hz), suggesting the presence of soft soil layers with sediment thickness exceeding 30 meters. The amplification factor mostly ranges between 1 and 3.5, with some points reaching 6, indicating a high potential for ground motion amplification. The seismic vulnerability index varies from 1 to 17, with the highest values in densely populated residential areas in the southern part of the study zone. Kalongan Village exhibits a high level of soil vulnerability, especially in areas with high amplification and seismic vulnerability index values. These findings can serve as a basis for developing landslide disaster mitigation strategies, including safer land use planning for the community.